Tingkat Penerimaan Program Komunikasi Digital ‘Jelajah Virtual’ Monumen Pers Nasional Pada Masa Pandemi Covid-19 - Wijaya, Niken; Pawito, Pawito; Rahmanto, Andre Novi (Jurnal Pekommas, 2022)
- During the Covid-19 pandemic, there were government regulations calling for the closure of non-essential public services, aiming to reduce the risk of spreading the Covid-19 virus. As a result, the convenience of direct interaction and communication between service workers and the public is disrupted. As a solution, digital-based interaction and communication programs are used to overcome these obstacles. Even so, it was not easy when you first used the program during the early days of the Covid-19 pandemic. Especially for public service officers who are required to provide optimal service to the public. Therefore, this research specifically aims to find out the level of acceptance and use of technology for public service workers (museum guides) in the digital communication program "Virtual Exploration" at the National Press Monument during the Covid-19 pandemic. This research uses the case study method through the Event Structure Analyst (ESA) approach and the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. The results of the study show that Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, Habit are related to the level of acceptance and use of technology in the National Press Monument's "Virtual Exploration" program during the Covid-19 pandemic. So it can be concluded that the level of acceptance of digital communication is carried out self-taught by adjusting the practice time which is not too long and easy to use and fun after getting used to it.